ISOLASI DAN IDENTIFIKASI SENYAWA GOLONGAN FLAVONOID DARI MADU K ELENGKENG (Nephelium longata L.) - Astiti Asih, Ida Ayu Raka; Ratnayani, Ketut; Swardana, Ida Bagus (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 1 Januari 2012, 2012)
The determination of anti free radical activity on longan honey (Nephelium longata L.) by DPPH method using UV-Vis sphectrophotometry and identification of chemical compound in non polar and semi polar fraction have been done. Longan honey was diluted with methanol and then partied by n-hexane and ethyl acetate. The absorbance was measured at 497 nm, 517 nm, and 537 nm for the DPPH concentration of : 0,001%, 0,002%, 0,003%, and 0,004% and the chemical compound was identified by phytochemical method. The result showed that part of n-hexane and ethyl acetate probably consist of chemical compound of isoflavone and value of anti free radical activity on longan honey in semi polar fraction was higher than in non polar fraction which were 91,71% and 77,68% at DPPH concentration of 0,001% (b/v).
Keywords: longan honey, free antiradical activity, DPPH method, n-hexane fraction, ethyl acetate fraction